Nerve Growth Factor Homology in the Nerve Regeneration-Conditioned Fluid of Rabbits and Rats - Ye, Y.; Li, Q.F.; Li, L. (Нейрофизиология, 2015)
We analyzed the homology of nerve growth factor (NGF) in the nerve regenerationconditioned fluid (NRCF) obtained from New Zealand white rabbits and SD rats. A nerve
regeneration chamber bridged distal and proximal ends of the severed rabbit sciatic nerve,
and the NRCF was extracted from such chamber. The supernatants and precipitates of nerve
tissue of rabbits and rats were extracted from the sciatic nerves by grinding and centrifugation.
An antigen-antibody reaction was detected by the ELISA technique using rabbit anti-mouse
NGF as primary antibody and goat anti-rabbit IgG as secondary antibody. Antigen-antibody
reactions were detected in all the above-mentioned samples obtained from rabbits and rats.
The intensity rank of an antigen-antibody response for different samples was the following:
rabbit NRCF > rabbit nerve tissue precipitation fluid > rabbit nerve tissue fluid supernatant >
> rat nerve tissue fluid supernatant. Thus, there is high homology of the molecular structure
of NGF in the NRCFs obtained from rabbits and rats (i.e., animals belonging to different
taxonomic groups of mammals). Ми аналізували молекулярну гомологію росту нервів (NGF) у
кондиційованій процесом нервової регенерації рідині (NRCF),
котру отримували від новозеландських білих кролів та щурів
лінії SD. Нейрорегенеративна камера з’єднувала дистальний
та проксимальний кінці перерізаного сідничного нерва у кролів, і NRCF відбирали з такої камери. За допомогою гомогенізації та центрифугування з тканини сідничних нервів кролів
та щурів готували супернатанти та преципітати. Реакцію антиген–антитіло виявляли за допомогою методики ELISA, використовуючи первинні антитіла щодо мишачого NGF та вторинні козячі антитіла щодо кролячого імуноглобуліну. Реакції
антиген–антитіло виявлялися в усіх вищезгаданих зразках,
отриманих від кролів та щурів. Послідовність інтенсивностей
відповідей антиген-антитіло у різних зразках була такою: кроляча NRCF > преципітат із нервової тканини кроля > супернатант із нервової тканини кроля > супернатант із нервової
тканини щура. Отже, молекулярна структура зразків NGF, що
знаходяться в NRCF, отриманій від кролів та щурів (тобто тварин, котрі належать до різних таксономічних груп ссавців), демонструє високий рівень гомології.